2011
DOI: 10.1186/1471-2318-11-49
|View full text |Cite
|
Sign up to set email alerts
|

Lighting and perceptual cues: Effects on gait measures of older adults at high and low risk for falls

Abstract: BackgroundThe visual system plays an important role in maintaining balance. As a person ages, gait becomes slower and stride becomes shorter, especially in dimly lighted environments. Falls risk has been associated with reduced speed and increased gait variability.MethodsTwenty-four older adults (half identified at risk for falls) experienced three lighting conditions: pathway illuminated by 1) general ceiling-mounted fixtures, 2) conventional plug-in night lights and 3) plug-in night lights supplemented by la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 26 publications
1
35
0
2
Order By: Relevance
“…Sight and visibility are important for good perception; therefore, it is important to provide light that will support the perceptual system. At night, light levels should be dim and allow for safe navigation, especially in bedrooms and bathrooms [81,[83][84][85]. It is also important to encourage older people to increase their exposure to light-dark patterns as part of their wellness program.…”
Section: Future Perspectivementioning
confidence: 99%
“…Sight and visibility are important for good perception; therefore, it is important to provide light that will support the perceptual system. At night, light levels should be dim and allow for safe navigation, especially in bedrooms and bathrooms [81,[83][84][85]. It is also important to encourage older people to increase their exposure to light-dark patterns as part of their wellness program.…”
Section: Future Perspectivementioning
confidence: 99%
“…A series of completed investigations have examined the effects of various forms of indoor night lighting for older people [4547]. These studies found that at comparable low illumination levels, indoor lighting systems that enhanced horizontal and vertical (H/V) spatial elements were associated with the highest levels of performance on standardised tests of gait and balance.…”
Section: Introductionmentioning
confidence: 99%
“…Lighting affects elderly individuals' ability to acquire visual information while moving in the environment. Age-related changes in vision may result in severely impaired balance control, leading to an increased risk of trip-related falls which more commonly occur among older adults 14) .…”
Section: Introductionmentioning
confidence: 99%
“…Low vision is correlated with poor performance in crossing obstacles 13) . Even small reductions in visibility affect the balance of the elderly 14) . Older adults with disordered gait show more variable and less steady gait while walking under dim lighting conditions 15) .…”
Section: Introductionmentioning
confidence: 99%